Clinical and Radiological Characteristics of Spondyloarthropathy - Yasemin Turan; Mehmet Tuncay Duruöz; Lale Cerrahoğlu (Archives of Rheumatology, 2008)
Objective: The objective of this study is to determine the clinical characteristics of patients with spondyloarthropaties (SpA). Patients and Methods: One hundred -twenty patients that match European Spondyloarthropaties Study Group (ESSG) diagnostic criteria, were included in this study. There were 48 ankylosing spondylitis (AS), 42 reactive arthritis (ReA), 9 psoriatic arthritis (PsA), 3 enteropathic arthritis (EA) and 18 undifferentiated SpA (uSpA) patients. Demographic data, clinical parameters and grade of sacroiliitis were assessed. Enthesitis were evaluated by the Mander Enthesis Index (MEI). Bath Ankylosing Spondylitis Disease Activity Index (BASDAI) and Bath Ankylosing Spondylitis Functional Index (BASFI) evaluated disease activity and functional status in AS patients, respectively. Results: The most frequently seen symptom was night pain (55.1%) and the most frequently seen radiographic involvement was right sacroiliitis ( 95.8%). Epin calcanei was most frequently observed in PsA (55.5%) and EA (33.3%) patients. The incidence of enthesitis in patients with SpA was 86.7%. Uveitis and heel pain were most commonly found respectively in AS (16.7%), and ReA (47.6%) patients. Conclusion: Whereas patients with SpA had similar clinical symptoms, their most common complaint was night pain. We think that it should be keep in mind while medical treatment is put in order. (Rheumatism 2008; 23: 46-51)